Regional lymph node metastasis in colon adenocarcinoma, second collection series - Maras, Gordan; Lindvall, Martin; Lundstrom, Claes (AIDA Data Hub, 2020)
Whole slide pathology images from regional lymph node metastasis in colon adenocarcinoma produced at Region Gävleborg Clinical Pathology and Cytology department. Consists of fifty chronologically consecutive cases. This dataset represents a second collection series in connection to the LNCO dataset using different collection and annotation parameters.
Keywords: Pathology; Annotated; Whole slide imaging; Lymph nodes; Cancer; Colon; Adenocarcinoma; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi